90.9k views
1 vote
(½) (6x + 3) = 7 – (3x + 1)

1 Answer

6 votes


\tt Step-by-step~explanation:

To solve for x, we have to remember to isolate the variable.


\tt Step~1:

For 1/2, we can make that 0.5, since their values are equivalent. Our equation:


\tt (0.5)(6x+3)=7-(3x+1)

Let's distribute the 0.5 first.


\tt 0.5*6x=3x\\0.5*3=1.5


\tt Step~2:

Now, let's simplify the right side of the equation. We have to distribute the negative to 3x and 1.


\tt -1*3x=-3x\\-1*1=-1

Then, we simplify the entire expression.


\tt 7-3x-1=-3x+6


\tt Step~3:

Our equation now:


\tt 3x+1.5=-3x+6

Let's add 3x to the right and 3x to the left to simplify the -3x on the right side of the equation.


\tt 3x(+3x)+1.5=-3x (3x)+6\\6x+1.5=6


\tt Step~4:

Let's do the same thing we did in Step 3 to 1.5. Subtract 1.5 on both sides of the equation.


\tt 6x+1.5(-1.5)=6(-1.5)\\6x=4.5


\tt Step~5:

Finally, we divide both sides by 6 to isolate x.


\tt (6x)/(6) =x\\(4.5)/(6)= 0.75~or~(3)/(4)


\large\boxed{\tt Our~final~answer:~x=0.75~(or~(3)/(4))}

User Boson
by
5.7k points